2001
DOI: 10.1103/physrevlett.86.4851
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Invar Effect in Fe-Ni Alloys

Abstract: We have measured the pressure-volume (P-V) relations for cubic iron-nickel alloys for three different compositions: Fe 0.64Ni (0.36), Fe 0.55Ni (0.45), and Fe 0.20Ni (0.80). It is observed that for a certain pressure range the bulk modulus does not change or can even decrease to some minimum value, after which it begins to increase under still higher pressure. In our experiment, we observe for the first time a new effect, namely, that the Fe-Ni alloys with high Ni concentrations, which show positive thermal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
65
0
11

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 10 publications
11
65
0
11
Order By: Relevance
“…In material synthesis, pressure adds a new dimension in creating exotic alloys and properties [615][616][617][618][619]. The formation of extended solids (polymers) is a common observation under HP, e.g., polymeric cg-N [587,620].…”
Section: High Pressure Chemistrymentioning
confidence: 99%
“…In material synthesis, pressure adds a new dimension in creating exotic alloys and properties [615][616][617][618][619]. The formation of extended solids (polymers) is a common observation under HP, e.g., polymeric cg-N [587,620].…”
Section: High Pressure Chemistrymentioning
confidence: 99%
“…3 These phenomena are only found by either using extreme conditions (such as high-pressure techniques 4 ) or new synthesis routes [such as mechanical alloying (MA)]. As is well known, the stable state of Fe at room temperature and atmospheric pressure has a bcc crystal structure with a lattice parameter a of about 2.87 Å, the so-called ␣-Fe phase.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] It has been observed the interdependence of the latter two variables in Ni-rich Fe-Ni compositions, where LS noncollinear magnetic ordering can be induced under pressure, giving rise to invar behavior. 33 In a previous work, we shown that the magnitude of the Curie temperature, T C , of an standard commercial Fe 64 Ni 36 powder sample can be increased in ⌬T C ϳ70 K, by means of a severe mechanical processing, using a high-energy ball mill, followed by a heating up to 1073 K, while the invar character is maintained and its temperature range enlarged as well. 34 Previously, Dumpich et al 35 already observed in "asprepared" Fe 65 Ni 35 evaporated thin films an increase in the T C value of ca 200 K, accompanied by an enhancement of 20% in the saturation magnetization, M s .…”
Section: Introductionmentioning
confidence: 99%